Customer Satisfaction Role in Mediating the Influence of Service Quality and Promotional Appeal on Electronic Word of Mouth - Putu Dio Artha Pratama; Ni Wayan Sri Suprapti (International Journal of Social Science and Business, 2023)
The rapid development of technology has a role in the relationship between business owners and customers. This is shown by the many messages in the form of reviews or recommendations submitted by customers via the internet or also called Electronic Word of Mouth (E-WOM). This study aims to analyze the role of customer satisfaction in mediating the effect of service quality and promotional attractiveness on electronic word of mouth. The population in this study consists of GoFood service users on the GoJek application in Bali represented by three regencies and one city, and the exact number cannot be mentioned or calculated (unlimited). The sampling method used in this study was purposive sampling. In this study, inferential statistics used Structural Equation Modeling (SEM) based on Partial Least Square (PLS) analysis. Data collection was carried out using questionnaires in the form of Google Forms distributed through social media. The results showed that the quality of service and the attractiveness of promotions had a positive and significant effect on customer satisfaction. The quality of service has a positive and significant effect on electronic word of mouth, while the attractiveness of promotion does not have a significant effect on electronic word of mouth. Customer Satisfaction has a positive and significant effect on Electronic Word of Mouth. Customer satisfaction partially mediates the effect of service quality on electronic word of mouth and fully mediates the effect of promotional attractiveness on electronic word of mouth. The implication of the results of this study is the importance of attention to service quality and promotional attractiveness in an effort to increase customer satisfaction and E-WOM.